2021
DOI: 10.5014/ajot.2021.041277
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver Perspectives on School Participation Among Students With Craniofacial Microsomia

Abstract: Importance: Knowledge of unmet school participation needs for students with craniofacial microsomia (CFM) can inform decisions regarding intervention support. Objective: To compare students with and without CFM on school participation (i.e., frequency, involvement, desire for participation to change) and caregivers’ perceptions of environmental support for participation in occupations. Design: Cross-sectional design using secondary analyses of a subset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…Children with microtia in this cohort achieved comparable school results to age matched controls which is a highly relevant finding in light of the potential effects of microtia on hearing, self-confidence and absence from school to attend outpatient appointments and surgical inpatient stays. It has been previously reported that patients with craniofacial microsomia may be disadvantaged in academic settings owing to restricted participation ( 37 ), however comparable academic attainment was achieved in Maths, Science and English in our cohort at 10–11 years of age. Further validation of this finding could be attained through an analysis of GCSE and A-level data to ascertain whether any latent effects on academic attainment manifest later in life.…”
Section: Discussionsupporting
confidence: 48%
“…Children with microtia in this cohort achieved comparable school results to age matched controls which is a highly relevant finding in light of the potential effects of microtia on hearing, self-confidence and absence from school to attend outpatient appointments and surgical inpatient stays. It has been previously reported that patients with craniofacial microsomia may be disadvantaged in academic settings owing to restricted participation ( 37 ), however comparable academic attainment was achieved in Maths, Science and English in our cohort at 10–11 years of age. Further validation of this finding could be attained through an analysis of GCSE and A-level data to ascertain whether any latent effects on academic attainment manifest later in life.…”
Section: Discussionsupporting
confidence: 48%
“…Skewed and missing data in predictive models raise questions about their generalizability to the population and the degree they may reinforce existing inequalities in healthcare settings ( 54 ). Therefore, future research on this topic should consistently report on family socio-economic status and child and/or youth race and ethnicity as well as improve sampling strategies to better represent child or youth gender ( 55 ) and the range of diagnoses in children who experience unmet participation need ( 56 , 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…23,29,30 In an American sample (N = 20), 75% had received multidisciplinary team care and 45% participated in at least a year of speech, physical, and/or occupational therapies. 20 In studies tracking a multisite North American sample of children with CFM (N = 107-121), 60% to 79% received intervention services, [31][32][33] including speech therapy (58%) and physical therapy (36%). Although communication difficulties were reported by more than two-thirds of those with aural atresia (total N = 254), only about half participated in speech therapy.…”
Section: Healthcare Experiencesmentioning
confidence: 99%
“…18 A pair of papers examined caregiver reports of school and community activities participation. 31,46 Although there were few differences between caregivers of children with CFM and healthy peers who had a history of participating in intervention services, there was a pattern of less involvement in school and community activities compared to peers with no service history, including less participation in organized physical activities, trips, clubs, and spending time with peers informally. 31,46…”
Section: Psychosocial Experiencesmentioning
confidence: 99%